Outcome after liver transplantation in elderly recipients (>65 years) — A single-center retrospective analysis. Issue 10 (October 2018) - Kollmann, Dagmar; Maschke, Svenja; Rasoul-Rockenschaub, Susanne; Baron-Stefaniak, Joanna; Hofmann, Michael; Silberhumer, Gerd; Györi, Georg P.; Soliman, Thomas; Berlakovich, Gabriela A.
Abstract: Background: Liver transplantation (LT) in elderly recipients is controversially discussed in the literature with only little data on long-term outcome available. We aimed to evaluate the safety and efficiency of LT in elderly recipients (>65 years). Methods: Between 1989–2016, 139 patients >65 years-old were listed for liver transplantation, and 76 (55%) were transplanted. Patient outcome and characteristics were evaluated separately for the time period before (1989–2004) and after (2005–2016) MELD-implementation. Post-transplant outcome was compared between the elderly cohort and LT-recipients aged 18–65 years (n = 1395). Results: Overall survival of patients >65 years was better in the MELD-era compared to the earlier period (1- and 5-year-survival: 73%, 60% vs. 69%, 37%, respectively; p = 0.055). The main differences between the two groups included higher recipient age (p = 0.001) and BMI (p = 0.001), higher donor age (p < 0.001), less need of intraoperative red blood cells (p = 0.008) and a lower number of postoperative rejections (p = 0.03) after 2004. Comparing the overall survival of patients transplanted in the MELD-era aged 18–65 years vs. >65 years displayed comparable 1- and 5 year-survival rates (81%, 68% vs. 73% and 60%, respectively, p = 0.558). Conclusion: In the modern era, outcome of patients receiving LT with >65 years is comparable to <65 year-old patients. After careful evaluation, patients >65 years old should be considered for LT.